2016
DOI: 10.1055/s-0036-1584210
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Radiographic Results of Indirect Decompression and Posterior Cervical Fusion for Single-Level Cervical Radiculopathy Using an Expandable Implant with 2-Year Follow-Up

Abstract: Indirect posterior cervical nerve root decompression and fusion performed by placing bilateral posterior cervical cages in the facet joints from a posterior approach has been proposed as an option to treat select patients with cervical radiculopathy. The purpose of this study was to report 2-year clinical and radiologic results of this treatment method. Patients who failed nonsurgical management for single-level cervical radiculopathy were recruited. Surgical treatment involved a posterior approach with decort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 15 publications
0
40
1
Order By: Relevance
“…One concern of posterior cervical cages is the potential to cause kyphosis. Several studies suggest that kyphosis does not occur with placement of the implants in the facet [4,20,7,3,17]. Overall and segmental spinal alignment were unchanged in this series.…”
Section: Discussionmentioning
confidence: 61%
“…One concern of posterior cervical cages is the potential to cause kyphosis. Several studies suggest that kyphosis does not occur with placement of the implants in the facet [4,20,7,3,17]. Overall and segmental spinal alignment were unchanged in this series.…”
Section: Discussionmentioning
confidence: 61%
“…Patient outcome was assessed with NDI in all studies, except for 3-which used NDI in addition to SF-12. 8,14,16 At 12-month follow-up, the earliest published series in the literature reported significant improvements in the NDI (64.9 to 16.3). Additionally, the SF-12 physical component score (PCS), and SF-12 mental component score (MCS) improved from 34.6 to 45.4 and from 40.7 to 51.4, respectively.…”
Section: Patient-reported Outcome Measuresmentioning
confidence: 99%
“…Four of the included studies included patient reported outcomes (71.4%). 8,14,16,17 One study was a purely radiographic study 12 (14.3%) and another study was an analysis of a medical device registry (14.3%). 13 All studies, except 2, were limited to single-level interventions.…”
Section: Included Studies and Quality Of Evidencementioning
confidence: 99%
See 2 more Smart Citations